Effect of Organic Acids in Crossbred Weaned Piglets - Kavya, A; Reddy, G Nagi; Devasena, B; Suryanarayana, M V A N; Chakravarthi, Kalyana; Reddy, G Bhaskara (Indian Journal of Animal Nutrition, 2025)
The present study was aimed to evaluate the effect of dietary organic acids on growth performance, nutrient digestibility and fecal microflora of crossbred weaned piglets. A total of thirty weaned crossbred piglets (75% LWY × 25% Desi) with average body weight of 7.5 ±0.5 kg (2 months old) were randomly divided (CRD) into five homogenous treatments with six piglets in each. The dietary treatments were T1 (control) - Basal diet as per NRC (2012), T2 - Basal diet + 1.5% Citric acid, T3 - Basal diet + 1.5% Fumaric acid, T4 - Basal diet + 1.5% Benzoic acid, T5 - Basal diet + 1.5% blend of citric, Fumaric acid and Benzoic acids (each at 0.5%). Results revealed that piglets received the diet containing blend of organic acids improved (P < 0.05) the ADG, feed efficiency, nutrient digestibility (CP and EE) and reduced fecal E. coli counts as compared with piglets received individual organic acids and control. The highest (P < 0.05) weight gain was observed in piglets fed T5 or T4 diets, followed by T2 or T3 and lowest in control. There was no effect (P > 0.05) of organic acids on average daily feed intake of piglets of different treatments. The digestibility of CF (%) was higher (P < 0.05) in the piglets received organic acids (either individual or blend) as compared to control. The Salmonella count was higher (P < 0.05) in the piglets received organic acids (either individual or blend) as compared with control. The cost per Kg weight gain (Rs.) was found to be significantly (P < 0.05) higher in organic acid supplemented groups as compared to control. In conclusion, dietary supplementation of blend of organic acids at 1.5% indicated beneficial effects on growth performance and nutrient digestibility coexisting with reduced fecal microbiota